THE INFLUENCE OF CTENOCEPHALIDES GENUS PARASITES ON HEMATOLOGICAL INDICES OF INFESTED DOGS - Yevstafieva, V. О.; Horb, K. O. (Scientific Progress & Innovations, 2019)
Fleas are parasitic insects belonging to Siphonaptera genus. All of them have practically the same body constitution and way of life. Parasites are mainly classified according to one sign – the kind of animal they feed on. Fleas of Ctenocephalides genus are the most widely spread and adapted to the population of domes-tic dogs. Their parasitizing can be accompanied by allergic dermatitis, iron-deficiency anemia, and exhaus-tion of infested dogs. The research was conducted at the Laboratory of the Department of parasitology and veterinary-sanitary expert examination, at Poltava State Agrarian Academy and in veterinary service “Vet-expert”. The aim of the research was to study the effect of ctenocephaliasis causal agents on hematological indices of infested dogs depending on the infection intensity As a result of the conducted research it was es-tablished that blood-sucking insects negatively affect animal organism, moreover, the severity of the disease course depends on the infection intensity. So, in case of parasitizing 15 flea specimens on the animal body, the number of leucocytes in their blood significantly (P<0.05) increased (by 12.3 %), which was the result of increasing the number of eosinophiles (by 36.7 %). At the same time, the number of erythrocytes (by 8.4 %) and hemoglobin content (by 9.9 %) slightly decreased, but these changes did not have significant differences. In case of more infection intensity (16−47 flea specimens on the animal body), the signs of anemia were re-vealed in the examined dogs with significant (P<0.01) decrease in the number of erythrocytes (by 17.5 %) and the amount of hemoglobin (by 19.8 %) in their blood. The number of leucocytes also increases – by 19.8 % (P<0.001). The indices of leuco-formula are characterized by considerable changes in the dog blood at high infection intensity – the amount of eosiniphiles increases up to 9.00±0.89 % (2.4 times, P<0.01) and rod neutrophils up to 6.80±0.37 % (1.5 times, P<0.05) as compared with the indices of clinically healthy animals (3.80±0.80 and 4.40±0.81 %, respectively). The obtained data broaden the already existing ones concerning dog ctenocephaliasis pathogenesis and they enable to conduct not only specific, but also symp-tomatic therapy.